2015
DOI: 10.1177/1077546315591620
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective genetic algorithm fractional-order PID controller for semi-active magnetorheologically damped seat suspension

Abstract: Recently, fractional-order proportional-integral-derivative (FOPID) controllers are demonstrated as a general form of the classical proportional-integral-derivative (PID) using fractional calculus. In FOPID controller, the orders of the derivative and integral portions are not integers which offer more flexibility in succeeding control objectives. This paper proposes a multi-objective genetic algorithm (MOGA) to optimize the FOPID controller gains to enhance the ride comfort of heavy vehicles. The usage of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…The MR and ER semi active suspensions are the most popular dampers being used recently because they work effectively to provide a quick response for energy dissipation level in the low-mid frequency range. However, a poor performance can be generated in the high frequency rang due to the specific dynamic range of the ER and MR fluid [42,43].…”
Section: Type Of Suspension Systemsmentioning
confidence: 99%
“…The MR and ER semi active suspensions are the most popular dampers being used recently because they work effectively to provide a quick response for energy dissipation level in the low-mid frequency range. However, a poor performance can be generated in the high frequency rang due to the specific dynamic range of the ER and MR fluid [42,43].…”
Section: Type Of Suspension Systemsmentioning
confidence: 99%
“…PID stands for proportional, integral, and derivative and is a classical controller used for several control applications (Metered et al 2015;Kesarkar and Selvaganesan 2015;Niu 2014;Gad et al 2017;Tammam et al 2013;Abdelrassoul et al 2016;Chen and Chang 2006). The PID controllers are so designed that continuous attention of the operator is eliminated.…”
Section: Control Theory-pid Controlmentioning
confidence: 99%
“…It was observed that the GA-based optimized PID controller improves the dynamic performance of the active suspension system and improves stability. Gad et al (2017) implemented a fractional order PID controller to a semi-active seat suspension. PID parameters are tuned using multi-objective GA for a seat suspension system using the 6-DoF human body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are resources dealing with semiactive related fractional order control, i.e. for active passenger seat control design [16], for a semi-active suspension [17], as well as smart-based isolated structures [18]. Not addressing skyhook control principles, the nature of the aforementioned material is very different to the work presented in this paper.…”
Section: Introductionmentioning
confidence: 99%